A randomized, double-blind, positive-controlled, Phase-II clinical trial to evaluate efficacy and safety of Fuke Qianjin capsule in Pakistani patients with pelvic inflammatory disease - Shah, Muhammad Raza; Khan, Sehrosh Naz; Fatima, Samreen; Yao, Liangyuan; Yuan, Hongbo; Ullah, Shafi; Ainuddin, Jahanara; Zeng, Changqing; Zheng, Yiyang; Sahar, Najmus; Anwar, Shaista; Zhu, Meijun; et al. (Frontiers in Pharmacology, 2024)
Ethnopharmacological relevance: Pelvic inflammatory disease (PID) is a frequently occurring gynecological disorder mainly caused by the inflammation of a woman’s upper genital tract. Generally, antibiotics are used for treating PID, but prolonged use poses potential risks of gut bacterial imbalance, bacterial resistance, super bacteria production, and associated adverse reactions. Traditional Chinese medicine (TCM) has shown unique advantages in various ailments and has received widespread clinical research attention. Fuke Qianjin (FUKE) capsule is an approved National Medical Products Administration (NMPA License No. Z20020024) Chinese herbal prescription that has been widely used individually or in combination with other Western medicines for the treatment of various gynecological inflammatory diseases, including chronic cervicitis, endometritis, and chronic PID. Aim: This clinical trial was designed to assess the safety and efficacy of FUKE capsule in mild-to-moderate symptomatic PID patients. Materials and methods: This phase 2, randomized, double-blind, positive controlled clinical trial was conducted in mild-to-moderate symptomatic PID patients at a single center in Pakistan from 21 September 2021 to 11 March 2022. Eligible female participants were randomly assigned to a test and a control group with a ratio of 1:1. The test group subjects received two metronidazole (METRO) tablets and one doxycycline hyclate (DOXY) simulant at a time, twice daily for 14 days, and two Fuke Qianjin (FUKE) capsules, three times a day after a meal for 28 days. Subjects in the control group received two METRO tablets and one DOXY tablet at a time, twice daily for 14 days, and two FUKE simulant capsules, three times a day after meal for 28 days. The primary efficacy outcome was an improvement in pelvic pain symptoms assessed through a visual analog scale (VAS). The secondary outcomes were the improvement in secondary efficacy symptoms like local physical signs, clinical assessment of leucorrhea and cervical secretions through laboratory examination, and improvement in the maximum area of pelvic effusion assessed through gynecological ultrasound after the treatment. The safety outcomes were assessed through vital signs, laboratory tests, electrocardiogram findings, and adverse events/serious adverse events. Results: A total of 198 subjects with active PID were randomly assigned to a test group (n = 99) and a control group (n = 99). The baseline characteristics of the subjects in the two groups were similar. In the intention-to-treat analysis, the primary efficacy was 84.9% for the test group and 71.6% for the control group, with a statistically significant difference (p = 0.0370; 95% CI −0.2568 to −0.0088). The secondary clinical efficacy was 88.4% for the test group and 82.7% for the control group, with no significant difference (p = 0.2977; 95% CI −0.1632 to 0.0501). The improvement in local physical signs was 95.8% for the test group and 76.9% for the control group, with no significant difference (p = 0.0542; 95% CI −0.3697 to −0.0085). The inter-group non-inferiority comparison showed that the upper limit of the 95% CI was less than 0.15 and thus met the non-inferiority requirements of the test group to the control group. The results of clinical signs of leucorrhea and cervical secretions showed that there was no difference in the rate of improvement between the test and control groups, indicating that FUKE was non-inferior to DOXY. A total of 14 adverse events in eight subjects were observed in the trial, with an incidence rate of 4.7%. Four subjects in each group experienced seven adverse events with 4.5% and 4.8% incidence rates of adverse reactions in the test and control groups, with no statistically significant differences (p = 0.2001). No serious adverse events occurred in the trial. Conclusion: The results of this trial indicate that the test drug (Fuke Qianjin capsule) is non-inferior to the control drug (doxycycline hyclate tablet) in treating mild-to-moderate PID patients with comparable efficacy, safety, and tolerability to the control drug. Clinical Trial Registration:www.clinicaltrials.gov, identifier NCT04723069.